Quercetin and tanshinone prevent mitochondria from oxidation and autophagy to inhibit KGN cell apoptosis through the SIRT1/SIRT3-FOXO3a axis: Quercetin and tanshinone prevent cell apoptosis via SIRT1/SIRT3 - Wan, Qingzhi; Tang, Lisha; Jin, Kaili; Chen, Xuanyi; Li, Yinghuan; Xu, Xiaofeng (Cellular and Molecular Biology, 2024)
Granulosa cells are somatic cells located inside follicles that play a crucial role in the growth and development of follicles. Quercetin and tanshinone are two key monomers in traditional Chinese medicine that have antioxidant and anti-aging properties. The KGN cell apoptosis model caused by triptolide (TP) was employed in this work to investigate granulosa cell death and medication rescue. Quercetin and tanshinone therapy suppressed KGN cell death and oxidation while also regulating the expression of critical apoptosis and oxidation-related markers such as B-cell lymphoma-2 (Bcl-2) and Bcl-2-associated X protein (Bax). Further research revealed that the effects of Quercetin and Tanshinone were accomplished via deacetylation of FOXO3A in the cytoplasm and mitochondria via the SIRT1/SIRT3-FOXO3a axis. In summary, Quercetin and tanshinone protect KGN cells from apoptosis by reducing mitochondrial apoptosis and oxidation via the SIRT1/SIRT3-FOXO3a axis.